Redefining the Scholar-Athlete - Cross, Joseph L.; Fouke, Bruce W. (Frontiers in Sports and Active Living, 2019)
Successful Scholar-Athletes are physically, intellectually, and emotionally committed to high-level achievement in both their academic and sport endeavors. This requires development of an integrated skill-set that includes teamwork, a strong work ethic, commitment, leadership, time management, and physical and emotional health. The identity crosses all perceived boundaries of race, gender, ethnicity, sexual orientation, religion, disability, social and economic status.A nationwide paradigm shift is urgently needed to recognize and tap into these skills for all scholar-athletes, which are the same tools required to succeed in all professions from science and technology to law, medicine, business and the arts. This article addresses the misperceptions and low expectations that much of our society has for the high school and collegiate Scholar-Athlete. While recognizing the efforts of programs that are working toward recalibrate the high school athlete’s self perceptions, awaken recognition of their own academic potential, and permit them to achieve successful careers and make invaluable professional contributions to society.